Construction of hpaA gene from a clinical isolate of Helicobacter pylori and identification of fusion protein - Mao, Ya-Fei (World J Gastroenterol, 2003)
AIM: To clone hpaA gene from a clinical strain of Helicobacter pylori and to construct the expression vector of the gene and to identify immunity of the fusion protein. METHODS: The hpaA gene from a clinical isolate Y06 of H. pylori was amplified by high fidelity PCR. The nucleotide sequence of the target DNA amplification fragment was sequenced after T-A cloning. The recombinant expression vector inserted with hpaA gene was constructed. The expression of HpaA fusion protein in E.coli BL21(DE3) induced by IPTG at different dosages was examined by SDS-PAGE. Western blot with commercial antibody against whole cell of H. pylori as well as immunodiffusion assay with self-prepared rabbit antiserum against HpaA fusion protein were applied to determine immunity of the fusion protein. ELISA was used to detect the antibody against HpaA in sera of 125 patients infected with H. pylori and to examine HpaA expression of 109 clinical isolates of H. pylori. RESULTS: In comparison with the reported corresponding sequences, the homologies of nucleotide and putative amino acid sequences of the cloned hpaA gene were from 94.25%-97.32% and 95.38%-98.46%, respectively. The output of HpaA fusion protein in its expression system of pET32a-hpaA-BL21(DE3) was approximately 40% of the total bacterial proteins. HpaA fusion protein was able to combine with the commercial antibody against whole cell of H. pylori and to induce rabbit producing specific antiserum with 1:4 immunodiffusion titer after the animal was immunized with the fusion protein. 81.6% of the serum samples from 125 patients infected with H. pylori (102/125) were positive for HpaA antibody and all of the tested isolates of H. pylori (109/109) were detectable for HpaA. CONCLUSION: A prokaryotic expression system with high efficiency of H. pylori hpaA gene was successfully established. The HpaA expressing fusion protein showed satisfactory immunoreactivity and antigenicity. High frequencies of HpaA expression in different H. pylori clinical strains and specific antibody production in H. pylori infected patients indicate that HpaA is an excellent and ideal antigen for developing H. pylori vaccine.